Effect of Emotional Biases on Investor’s Decision Making in Nigeria - Akinkoye, Ebenezer Y.; Bankole, Oluwaseun E. (International Journal of Business and Management Future, 2020)
The study examined emotional biases and its effect on investor’s decision making in Nigeria Primary data were employed and the population consists of clients of the top 10 stockbroking firms registered by the Nigerian Stock Exchange as at 31st January, 2018. These firms were selected because they contributed to 68.72% of total value of transactions as at 31st January, 2018. Data on emotional biases and investment decision making among investors in Nigeria were obtained through structured questionnaire which was administered to 30 clients of each stockbroking firm, totalling 300. Data analysis was done using percentages and logistic regression analysis. Findings showed that emotional biases, represented by loss-aversion bias, overconfidence bias, regret-aversion bias and herding bias were prevalent to Nigerian investors and also significantly influenced investor’s decision making in Nigeria. The study suggests that investors should improve the understanding of various emotional biases and traits exhibited by them, adopt a suitable decision technique to avoid this and seek experts’ opinion when making investment decisions.